SKRINING FITOKIMIA DAN PENETAPAN KADAR FENOL TOTAL PADA EKSTRAK DAUN NANGKA (Artocarpus heterophyllus), CEMPEDAK (Artocarpus integer), dan TARAP (Artocarpus odoratissimus) ASAL DESA PENGARON KABUPATEN BANJAR - Muhammad Ikhwan Rizki; Nurlely Nurlely; Fadlilaturrahmah Fadlilaturrahmah; Ma’shumah Ma’shumah (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2021)
The leaves of jackfruit (Artocarpus heterophyllus), cempedak (Artocarpus integer), and tarap (Artocarpus odoratissimus) are used empirically by the people of Desa Pengaron, Banjar Regency for treat antimalarials, antidiabetic, abdominal pain, and cancer. The secondary metabolites of the phenol group are responsible for various plant activities. This study aims to determine of compounds and total phenol content in leaves of jackfruit (A. heterophyllus), cempedak (A. integer), and tarap (A. odoratissimus). The leaf samples were oven-dried, then the leaf powder was extracted using ethanol. Phytochemical screening was carried out on the extract using reagents, and phenol content was determined using a spectrophotometer UV-Vis. The results showed that the extracts of leaves jackfruit (A. heterophyllus), cempedak (A. integer), and tarap (A. odoratissimus) contained phenol, flavonoids, and tannins. Total phenol content of leaves A. heterophyllus, A. integer and A. odoratissimus were 13,174 ± 1,378 mgGAE / gram extract, 37,204 ± 2,202 mgGAE / gram extract, and 35,886 ± 0.890 mgGAE / gram extract.